MORPHOLOGICAL CHANGES OF CORTICOSTEROCYTES AND CHROMAFFIN CELLS AFTER 1 MONTH OF CHEMICAL CASTRATION UNDER CONDITIONS OF CORRECTION WITH QUERCETIN - Skotarenko, T.A. (World of Medicine and Biology, 2023)
It is well known that endocrine pathology is a leading disease in the morbidity structure of the Ukrainian population. It is important to study the metabolic effects of hormones of the structural components of the hypothalamic-pituitary-gonadal axis on other peripheral endocrine glands and body organs. Modern research on testosterone proves its effect on the biochemical processes of nervous tissue, liver, organs of the male and female reproductive systems, and others. The paper describes the main morphological changes of corticosterocytes in the adrenal cortex area and endocrinocytes of the adrenal medulla of white rats during the correction of central deprivation of testosterone synthesis during 1 month of the experiment. It was found that the inhibition of testosterone synthesis caused reactive changes in both - corticosterocytes and chromaffin cells, manifested at the microscopic level by the variability of morphometric parameters.
Keywords: chemical castration; corticosterocytes; chromaffin cells; adrenal gland; correction